Cancel Culture di Media Sosial: Dampaknya terhadap Kebebasan Berpendapat dan Resiliensi Psikologis Mahasiswa - Ike Dian Puspita Sari; Nurcholis Sunuyeko; Anita Kurnia Rachman (Universitas Insan Budi Utomo, 2026)
This study explores the phenomenon of cancel culture and its impact on freedom of speech and the psychological resilience of university students in Indonesia. Employing a qualitative approach with an existential phenomenological design, data were collected through in-depth interviews with 15 students who had been involved in the digital cancellation ecosystem as perpetrators, victims, or passive bystanders. The results reveal that cancel culture has mutated from an accountability instrument into a repressive form of digital vigilantism. Key findings indicate a massive chilling effect, where students obsessively practice self-censorship of their opinions due to the fear of destructive social exclusion. Furthermore, the study identifies severe psychological impacts on